Caatinga Revisited: Ecology and Conservation of an Important Seasonal Dry Forest. (1st August 2012) - de Albuquerque, Ulysses Paulino; de Lima Araújo, Elcida; El-Deir, Ana Carla Asfora; de Lima, André Luiz Alves; Souto, Antonio; Bezerra, Bruna Martins; Ferraz, Elba Maria Nogueira; Maria Xavier Freire, Eliza; Sampaio, Everardo Valadares de Sá Barreto; Las-Casas, Flor Maria Guedes; de Moura, Geraldo Jorge Barbosa; Pereira, Glauco Alves; et al.
Abstract : Besides its extreme climate conditions, the Caatinga (a type of tropical seasonal forest) hosts an impressive faunal and floristic biodiversity. In the last 50 years there has been a considerable increase in the number of studies in the area. Here we aimed to present a review of these studies, focusing on four main fields: vertebrate ecology, plant ecology, human ecology, and ethnobiology. Furthermore, we identify directions for future research. We hope that the present paper will help defining actions and strategies for the conservation of the biological diversity of the Caatinga.